The Complex Interplay Between Dental Anxiety, Generalized Anxiety, and Dental Neglect and Oral Health Quality of Life in the General Public - Bin Rahmah, Abdullah S.; Alsaif, Mohammed I.; Naser, Abdallah Y. (Healthcare (Basel), 2025)
Background: Dental anxiety and generalized anxiety are common psychological conditions and can lead to poor oral health and avoidance behavior. This research aims to study the complex interplay between dental anxiety, generalized anxiety, dental neglect, and oral health-related quality of life (OHRQoL) in the general public. Methods: This is an online survey study that was conducted between August to September 2024 in Saudi Arabia and Jordan. Four previously validated instruments were used in this study. This study made use of the Modified Dental Anxiety Scale, the General Anxiety Disorder-7, dental neglect scale, and the Oral Health Impact Profile-14. Mediation analysis was conducted using the PROCESS macro (Model 4) to explore whether dental anxiety and dental neglect mediates the relationship between generalized anxiety and OHRQoL. Results: This study had 2704 participants in total. Higher anxiety levels were associated with slightly lower dental neglect and significantly poorer OHRQoL. Generalized anxiety significantly predicted dental anxiety, with a coefficient of b = 0.275 (p < 0.001). Both generalized anxiety and dental anxiety were significant predictors of OHRQoL, with generalized anxiety showing stronger effect. Dental anxiety partially mediates the impact of generalized anxiety on oral health-related quality of life, while a strong direct effect remains. Conclusions: Dental neglect served as a minor mediator, and the primary relationship between anxiety and oral health-related quality of life is direct. Moreover, dental anxiety partially mediates the impact of generalized anxiety on oral health-related quality of life, while a strong direct effect remains.